Industry in Africa - Ewing, A. F. (London : New York [etc.] , Oxford U.P., 1968)
This book examines he problems of industry in Africa and includes topics: the role of industry in development; patterns of industry in Africa; industrial growth outside Africa; trade and integration; capital formation; pre-requisite of industrial development; and agents of industrialization.
Includes bibliographical references.
lje 14/05/2018
Loans
Keywords: Industries; Africa